FACTORS AFFECTING THE WELFARE OF ONLINE DRIVERS IN BANDAR LAMPUNG CITY - Teguh Santoso; Herry Goenawan Soedarsa (ZILLZELL MEDIA PRIMA, 2024)
This study aims to identify the influence of online transportation factors and strategy factors on the welfare of online drivers in the city of Bandar Lampung. This study used quantitative methods using a sample of 100 respondents. The analysis techniques used in this study are validity tests and reliability tests, classical assumption tests, multiple liner regression tests, hypothesis tests and determination coefficient tests, data processed using the IBM SPSS 25 application (2023). Based on the results obtained in this study that online transportation has a positive and significant effect on driver welfare, strategies have a positive and significant effect on driver welfare. Then together online transportation and strategies have a positive and significant effect on the welfare of drivers. Online transportation and strategies can be an effective approach for drivers to meet their welfare. With increasingly fierce driver competition, this research can be a place for drivers to be able to fulfill their welfare.